2014
DOI: 10.3390/ijerph111010737
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Health Impacts of Drought in Brazil

Abstract: Drought is often a hidden risk with the potential to become a silent public health disaster. It is difficult to define precisely when it starts or when it is over, and although it is a climatological event, its impacts depend on other human activities, and are intensified by social vulnerability. In Brazil, half of all natural disaster events are drought related, and they cause half of the impacts in number of affected persons. One large affected area is the semiarid region of Brazil’s Northeast, which has his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 18 publications
0
84
0
5
Order By: Relevance
“…Drought can be a hidden risk with the potential to cause a public health disaster [87]. A SR of the health effects of drought found the main categories included: Nutrition-related effects; water-related disease (including Escherichia coli, cholera and algal bloom); airborne and dust-related disease (including coccidioidomycosis); vector borne disease (including malaria, dengue and West Nile Virus); mental health effects; and other health effects [88].…”
Section: Droughtmentioning
confidence: 99%
“…Drought can be a hidden risk with the potential to cause a public health disaster [87]. A SR of the health effects of drought found the main categories included: Nutrition-related effects; water-related disease (including Escherichia coli, cholera and algal bloom); airborne and dust-related disease (including coccidioidomycosis); vector borne disease (including malaria, dengue and West Nile Virus); mental health effects; and other health effects [88].…”
Section: Droughtmentioning
confidence: 99%
“…37 One study from Brazil found that semi-arid regions across 20 years made slower gains in population health when compared to the other regions of the country; namely, infant mortality rate, poverty, illiteracy and life expectancy regularly remained worse off. 38 Another crucial consideration for the Eastern Mediterranean Region is the interaction between food security and climate events in natural and human-induced disasters or political instability. 39 Protracted crises are the new norm, especially in EMR, with signi cant implications for vulnerability to extreme weather and climate events.…”
Section: Discussionmentioning
confidence: 99%
“…NTT has experienced annual severe drought within last ten years. Many efforts have been conducted to minimize the negative impacts of the drought such as in Sena et al (2014), WMO & GWP (2017) among others.…”
Section: Introductionmentioning
confidence: 99%